The role of C-reactive protein in predicting the severity of COVID-19 disease: A systematic review. (October 2021) - Yitbarek, Getachew Yideg; Walle Ayehu, Gashaw; Asnakew, Sintayehu; Ayele, Fanos Yeshanew; Bariso Gare, Moyeta; Mulu, Anemut Tilahun; Dagnaw, Fentaw Teshome; Melesie, Biruk Demissie
Since December 2019, coronavirus diseases-2019 (COVID-19) dispersed into 200 countries and affected more than 70 million people. The clear picture of the SARS-CoV-2 infection is still under investigation. In this review, we evaluated whether C-reactive protein biomarker is able to predict the clinical outcomes or correlated with the severity of COVID-19 disease. The databases MEDLINE, Hinari, Google Scholar, and Google search were used to find potential studies published from COVID-19 epidemic until May 2021. A format prepared in Microsoft Excel spreadsheet was used to extract the appropriate details from each original report. For further review, the extracted data were exported to STATA/MP version 16.0 software. Keywords including "COVID-19, " "SARS-CoV-2, " and "C-reactive protein, " among others were used to search relevant articles. Only studies which reported the average C-reactive protein value and COVID-19 disease stage outcomes were included. Twenty articles were included in the review. All studies found considerably higher level of C-reactive protein in patients with severe COVID-19 as compared to mildly infected patients. This review evidenced that it is still there for a given biomarker to early identify the state of progression in asymptomatic and/or mildly infected individuals into severe disease; the level of C-reactive protein may be used in predicting the likelihood of disease progression. Findings from this review showed level of C-reactive protein is a good biomarker to predict the severity of COVID-19 disease. Although COVID-19 researches are at the early stages, investigation of C-reactive protein levels throughout the disease course may have paramount importance for clinicians in early detection of severe manifestations and subsequently improve the prognosis. However, further large-scale studies are required to confirm these findings.